THE CHOICE OF PHARMACY PROFESSION AS A CAREER: UAE EXPERIENCE - Abduelkarem, Abduelmula; HAMRROUNI, Amar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Students decision to choose pharmacy as a future career is one of many difficult choices, they have to make as they enter the university, and it is a big decision as they have to live with the consequences the rest of their lives. Aim: The purposes of this study were to evaluate the student's reasons for selecting to study pharmacy major and gauge the student's perception and attitude regarding pharmacy education, pharmacists, and pharmacy profession. Methods: A cross-sectional survey-based study. Results: Family encouragement (213; 84.5%), personal interest (179; 71.0%), and to get a medical professional degree (199; 79.0%) were reported by the majority of the students under investigation as a personal reason to join pharmacy as a career. Interestingly, when participants were asked to show their opinion about the relationship between what they had studied and reality of the practice, almost half 25 (47.2%) reported no.â€ Conclusion: Despite the positive attitude of students to work as a member of health-care team, pharmacy curriculum in the colleges of pharmacy and pharmacy practice at the community level have to be revised and improved to meet students' expectation after graduation, to change student opinion regarding advising a family member or a friend to study pharmacy, and to help students to find a good relationship between the study and the reality of pharmacy practice. Keywords: Pharmacy students, Pharmacy education, Career preferences, United Arab Emirates, Educational and Practice Research.